2015
DOI: 10.1021/acssynbio.5b00164
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Central Carbon Metabolism for Improved Pathway Yields in Saccharomyces cerevisiae

Abstract: Engineering control of metabolic pathways is important to improving product titers and yields. Traditional methods such as overexpressing pathway enzymes and deleting competing ones are restricted by the interdependence of metabolic reactions and the finite nature of cellular resources. Here, we developed a metabolite valve that controls glycolytic flux through central carbon metabolism in Saccharomyces cerevisiae. In a Hexokinase 2 and Glucokinase 1 deleted strain (hxk2Δglk1Δ), glucose flux was diverted away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 74 publications
1
37
0
Order By: Relevance
“…The slower consumption of xylose as compared with glucose might also play a role in increasing isobutanol production. Recently, it has been shown that implementing a flux valve increases the yield of isobutanol from engineered S. cerevisiae (Tan, Manchester, & Prather, ). Endogenous hexokinases GLK1 and HXK2 were deleted alongside downregulation of HXK1 using a doxycycline‐inducible repressor, leading to a reduced rate of glucose phosphorylation and lowered glycolytic flux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slower consumption of xylose as compared with glucose might also play a role in increasing isobutanol production. Recently, it has been shown that implementing a flux valve increases the yield of isobutanol from engineered S. cerevisiae (Tan, Manchester, & Prather, ). Endogenous hexokinases GLK1 and HXK2 were deleted alongside downregulation of HXK1 using a doxycycline‐inducible repressor, leading to a reduced rate of glucose phosphorylation and lowered glycolytic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites were extracted and quantified from cells grown in the mid-exponential phase as described in the materials and methods. Each column represents one biological replicate while each row represents a single metabolite [Color figure can be viewed at wileyonlinelibrary.com] Recently, it has been shown that implementing a flux valve increases the yield of isobutanol from engineered S. cerevisiae (Tan, Manchester, & Prather, 2016). Endogenous hexokinases GLK1 and HXK2 were deleted alongside downregulation of HXK1 using a doxycycline-inducible repressor, leading to a reduced rate of glucose phosphorylation and lowered glycolytic flux.…”
mentioning
confidence: 99%
“…One set of tools for dynamic metabolic engineering are genetic "toggle" switches, which enable the inducible repression of genes including essential enzymes responsible for competitive metabolic fluxes [33][34][35][36][37][38][39][40]. A common essential and competitive metabolic pathway is the citric acid or tricarboxylic acid (TCA) cycle.…”
Section: Transcriptional Toggle Switchesmentioning
confidence: 99%
“…Moreover, the specific growth rate of engineered E. coli can be reduced by up to 50% without altering final biomass accumulation. The same strategy was then employed to develop a metabolite valve in S. cerevisiae for control of glycolytic flux through the central carbon metabolism [72]. This was demonstrated by diverting glucose flux away from glycolysis into a model pathway, gluconate, in a hexokinase 2 and glucokinase 1 deleted strain.…”
Section: Dynamic Control Of Competing Pathwaysmentioning
confidence: 99%